Beatrix Potter's gardening life : the plants and places that inspired the classic children's tales - McDowell, Marta (Timber Press, 2013)
Beatrix Potter's Gardening Life is the first book to explore the origins of Beatrix Potter's love of gardening and plants and show how this passion came to be reflected in her work. The book begins with a gardener's biography, highlighting the key moments and places throughout her life that helped define her, including her home Hill Top Farm in England's Lake District. Next, the reader follows Beatrix Potter through a year in her garden, with a season-by-season overview of what is blooming that truly brings her gardens alive. The book culminates in a traveler's guide, with information on how and where to visit Potter's gardens today.